ngaruh Kualitas Pelayanan Dan Harga terhadap Keputusan Pembelian Customer Serta Dampaknya pada Kepuasan Pelanggan (Studi Kasus : Maskapai PT. Lion Air Jakarta) - Nasution, Herlina; Maksum, Choirul; Derriawan (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
This study aims to determine how the influence of service quality and price to customer purchasing decisions and their impact on customer satisfaction (Case study: airline Lion Air). The data of this study were collected by using questionnaires distributed to the respondents. The results of this study concluded that the quality of service does not have an effect on the decision to purchase tickets or products of PT. Lion Air, Price has no effect on the decision of purchasing tickets or products of PT. Lion Air, Quality of service has an influence on product customer satisfaction PT. Lion Air, Price has influence to customer satisfaction of product of PT. Lion Air, Purchasing Decision has influence to customer satisfaction of PT. Lion Air.